Microbiological pathogens in fecal samples of foals during the first year of life - Jung, Clarissa; Gentil, Michaela; Müller, Elisabeth (Tierärztliche Praxis Ausgabe G: Großtiere / Nutztiere, 2024)
Objective The objective of the study was to investigate the age dependent occurrence of different infectious agents in foals with diarrhea.Material and Methods Fecal samples, which were submitted to a commercial laboratory for a PCR-profile “Foal Diarrhea Pathogens” from 01.01.2021 up to 31.12.2022 (n=144), were examined for Equine Coronavirus (ECoV), Lawsonia (L.) intracellularis, Rhodococcus (R.) hoagii (=R. equi), Clostridium (Cl.) perfringens toxin-encoding genes cpa, cpe, cpb, etx and netF, Clostridioides (C.) difficile toxin-encoding genes tcdA and tcdB, as well as Rotavirus A via PCR.Results Pathogens could be detected in a high proportion (42.9%) of the samples. Rotavirus A was the most prevalent pathogen in the current study, followed by clostridial species. Especially in foals younger than one month, netF-producing Cl. perfringens was detected frequently. In this age group, netF-producing Cl. perfringens was as prevalent as Rotavirus A. In comparison, R. hoagii, L. intracellularis and ECoV were detected rarely. Cl. perfringens toxin-encoding genes cpb and etx were not present in the examined samples. In general, the previously known age dependency of the investigated pathogens could be confirmed. Nevertheless, Rotavirus A and netF-positive Cl. perfringens could also be detected outside of the most susceptible age group. Coinfections with the examined pathogens had a low prevalence in the current study.Conclusions In general, the examined pathogens showed an age dependent occurrence, but infections in foals outside of the common age group could not be ruled out with certainty due to small sample numbers in some of the age groups. Although Rotavirus A was the most prevalent pathogen in this study, netF-producing Cl. perfringens is an important differential diagnosis, especially in newborn foals. The diagnostic approach in diarrheic foals should contain a broad spectrum of pathogens. This is not only important to detect coinfections, but also to detect shedders, in order to protect other horses in the stable.
Keywords: Foal diarrhea; Clostridial toxins; Rotavirus A; Equine Coronavirus; Lawsonia intracellularis; Rhodococcus hoagii